2020
DOI: 10.1101/2020.10.25.354308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheHistoplasma capsulatum DDR48Gene Is Required For Survival Within Macrophages, Response To Oxidative Stress, And Resistance to Antifungal Drugs

Abstract: Histoplasma capsulatum (Hc) is a systemic, dimorphic fungal pathogen that affects upwards of 500,000 individuals in the United States annually. Hc grows as a multicellular mold at environmental temperatures; whereas, upon inhalation into a human or other mammalian host, it transforms into a unicellular, pathogenic yeast. This manuscript is focused on characterizing the DNA damage-responsive gene HcDDR48. HcDDR48 was originally isolated via a subtractive DNA library enriched for transcripts enriched in the mold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…It has been shown to respond to a wide range of environmental stresses, including exposure to DNA damaging chemicals, heat-shock, osmotic stress, oxidative stress, DNA replication stress and exposure to antifungals (McClanahan and McEntee, 1986;Treger and McEntee, 1990;Miralles and Serrano, 1995;Karababa et al, 2004;Hromatka et al, 2005;Setiadi et al, 2006;Hao et al, 2009;Tkach et al, 2012;Mostafa and Awad, 2015). A recent study found that in H. capsulatum DDR48 confers some resistance to the antifungal azoles via the regulation of sterol biosynthesis (Reyes, 2019;Blancett et al, 2020), which is consistent with an increase in ddr48 expression in azole-resistant isolates of C. albicans (Mostafa and Awad, 2015). DDR48 is also known to be required for H. capsulatum pathogenicity and survival in macrophages, likely due a role regulating the enzymes needed to detoxify reactive oxygen species (ROS) (Blancett, 2019;Blancett et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to respond to a wide range of environmental stresses, including exposure to DNA damaging chemicals, heat-shock, osmotic stress, oxidative stress, DNA replication stress and exposure to antifungals (McClanahan and McEntee, 1986;Treger and McEntee, 1990;Miralles and Serrano, 1995;Karababa et al, 2004;Hromatka et al, 2005;Setiadi et al, 2006;Hao et al, 2009;Tkach et al, 2012;Mostafa and Awad, 2015). A recent study found that in H. capsulatum DDR48 confers some resistance to the antifungal azoles via the regulation of sterol biosynthesis (Reyes, 2019;Blancett et al, 2020), which is consistent with an increase in ddr48 expression in azole-resistant isolates of C. albicans (Mostafa and Awad, 2015). DDR48 is also known to be required for H. capsulatum pathogenicity and survival in macrophages, likely due a role regulating the enzymes needed to detoxify reactive oxygen species (ROS) (Blancett, 2019;Blancett et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that in H. capsulatum DDR48 confers some resistance to the antifungal azoles via the regulation of sterol biosynthesis (Reyes, 2019;Blancett et al, 2020), which is consistent with an increase in ddr48 expression in azole-resistant isolates of C. albicans (Mostafa and Awad, 2015). DDR48 is also known to be required for H. capsulatum pathogenicity and survival in macrophages, likely due a role regulating the enzymes needed to detoxify reactive oxygen species (ROS) (Blancett, 2019;Blancett et al, 2020). Regulating complex pathways in response to environmental factors is perfectly consistent with a potential role in the regulation of secondary metabolites such as pleuromutulin, which are known to be produced under specific environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…H. capsulatum RNA was isolated by mechanical disruption with 0.5 mm glass beads, extraction with TRIzol™ (Invitrogen), and precipitated with ethanol, as previously described (44,45). Genomic DNA was removed via DNase digestion and column purification using the PureLink™ RNA Mini Kit (Invitrogen).…”
Section: Gene Expression Analysismentioning
confidence: 99%